SİNTERLENMİŞ CR23C6 KARBÜR TOZUNUN DİFÜZYON KAYNAĞI YÖNTEMİ İLE YÜZEY KAPLAMA MALZEMESİ OLARAK ARAŞTIRILMASI - KOÇ, VAHDETTİN (Fırat Üniveristesi, 1999)
nı ÖZET Yüksek Lisans Tezi IIŞ Cr23C6 KARBÜR TOZUNUM DIFÜZYON IW Sİ İLİ VAHDETTİN KOÇ Fırat Üniversitesi Fen Bilimleri Enstitüsü letalurjî Eğitimi ÂnabiHim Dalı 1999 Sayfa: 79 Bu çalışmada ferrokrom tozlarının yüzey kaplama malzemesi olarak kullanılıp kullanılmayacağı araştırılmıştır. Bu maksatla Elazığ ferrokrom tesislerinden temin edilen tozlar, demir tozları ile %5,10,20 oranlarında ve bağlayıcı olarak da Ni ve Co kullanılarak sinterlenmiş. Elde edilen kompozit AISI 1010' dan parçalara difüzyon kaynağı yolu ile 1100 °C de basınç altında birleştirilerek, birleşme arakesitinin özellikleri incelenmiştir.VI As a result it was found that wear - resistance plates could be produced using ferro-chromium powder (Yıldırım, 1999) and these plates could be bonded with low C steels safely with diffusion bonding. n In the first chapter of the study, the subject was introduced, the powder metallurgy, ferro-chromium, solid-state boding methods in were discussed in the second, third and fourth chapters respectively. In the fifth chapter the experimental studies, in the sixth chapter the results of experiments were given. In the seventh and final chapter, the condusions and recommendations were presented.

SUMMARY tester Thesis INVESTIGATION OF SINTERED Cr23C6 POWDER AS SURFACE COATING MATERYAL VAHDETTİN KOÇ Fırat University Graduate School of Natural and Applied Sciences Department of Metallurgy Education 1999, Page: 79 in this study, usability of ferro-chromium powders as surface coating materials was investigated. With this aim powder provided from Elazig Ferro-Chromium Plant was mixed with iron powders having 2 %Co and then 2 %Ni, in proportions of 5, 10, and 20 percent. This mixtures were compacted under a load of 18 ton and sintered at 1100°C for 60 minutes. The composites produced were diffusion-bonded with AISI 1010 rectangular bars under bonding pressures of 2,5 MPa in 60 minutes. The bonding interface of the diffusion couples (AISI 1010-Cornposite) were examined with optical microscope, EDS, SEM and the hardness distributions were determined with Vickers Hardness Scale using a load of 3 Kg.VI As a result it was found that wear - resistance plates could be produced using ferro-chromium powder (Yıldırım, 1999) and these plates could be bonded with low C steels safely with diffusion bonding. n In the first chapter of the study, the subject was introduced, the powder metallurgy, ferro-chromium, solid-state boding methods in were discussed in the second, third and fourth chapters respectively. In the fifth chapter the experimental studies, in the sixth chapter the results of experiments were given. In the seventh and final chapter, the condusions and recommendations were presented. ©OKÛMANTASYON MERKEZÎ
Investigation of sintered Cr23C6 powder as surface coating materyal
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Eğitim ve Öğretim; Education and Training; Metalurji Mühendisliği; Metallurgical Engineering